Enhancing the fuel properties of tyre oil diesel blends by doping nano additives for green environments. (10th December 2019) - Kumaravel, S.T.; Murugesan, A.; Vijayakumar, C.; Thenmozhi, M.
Abstract: The waste tyres are deposited in landfills; it will cause severe health problems to human. To overcome this problem the present work is focused on converting waste tyre into oil and finding fuel properties towards clean environment by waste management. First the tyre oil blends 5%, 10%, 15% and 20% by volume with diesel and without cerium oxide nano additives are taken. The properties of the blends are tested as per the american society for testing and materials (ASTM) standard. Heating value, density, viscosity, flash and fire point have been measured for the above tyre pyrolysis oil and diesel blends. The experimental results shows the viscosity, density of all fuel blends are higher than diesel and flash & fire point, calorific value of all fuel blends are lower than diesel. In such a case cerium oxide nano additive was doped with tyre pyrolysis oil of 5%, diesel of 90% with cerium oxide nano additives 50 ppm (B5D90 + CeO2 50 ppm), tyre pyrolysis oil of 5%, diesel of 85% with cerium oxide nano additives 100 ppm (B5D85 + CeO2 100 ppm), tyre pyrolysis oil of 10%, diesel of 85% with cerium oxide nano additives 50 ppm (B10D85 + CeO2 50 ppm) and tyre pyrolysis oil of 10%, diesel of 80% with cerium oxide nano additives 100 ppm (B10D80 + CeO2 100 ppm) using solgel process, then all the fuel properties are increased compared to without nano additive blends. The experimental result shows the B5D85 + CeO2 100 ppm the value comparative to diesel. The morphological and structural studies of cerium oxide (CeO2 ) nano additives were illustrated by (XRD), scanning electron microscopy (SEM) and Fourier-transform infrared spectroscopy (FTIR). The Gas chromatography–mass spectrometry (GC-MS) and stability analysis was carried out for a prepared fuel. However, B5D85 + CeO2 100 ppm were found to have higher brake thermal efficiencies, higher NOX along with lower smoke emissions in association to diesel operation where also discussed in this paper. The discussion was directed by the dual reason of dropping the environmental impacts, though ahead of economical sustainability. These properties, environmental impact and financial viability reveals that the tyre pyrolysis diesel blends doped with CeO2 nano additives is a most affordable alternative fuel for compression ignition (CI) engine towards clean environments. Highlights: Tyre oildiesel blends doped with CeO2 nano additives showed properties to be applied as green fuel for cleaner environments. Blend properties highlight the complexity of the chemical interactions between the fuels. Characterization and stability analysis of cerium oxide nanoparticles shows better results. B5D85 + CeO2 100 ppm can be used normally in Diesel engines. Selling price of the tyre oil will be low as diesel.